The Using of Padlet on Students’ Communication and Collaboration Skill in Immune System Material - Meidina Rahmawati; Saiful Ridlo; Priyantini Widiyaningrum; Irsadi, Andin (Universitas Negeri Semarang, 2024)
Several 21st century skills such as students’ communication and collaboration skills are also not well honed during the pandemic learning. Another problem that arises in learning, especially Biology, is the characteristics of each Biology material that has complex concepts and problems. This causes students to often find it difficult to understand Biology material. The immune system material that discusses the working mechanisms in the body makes it more difficult for students to learn and causes students to experience misconceptions. This study aims to measure students’ communication and collaboration skills on the Immune System material assisted by the Padlet website. Padlet is commonly referred as an online whiteboard that allows educators and students to convey and share ideas/concepts and thoughts in the form of text, photos or videos in real time. This study is a pre-experimental study with a one-shot case study research design. The sample was taken using the purposive sampling method, so that 36 respondents were taken from high school students in grade XI (Phase F). The data collection techniques for this study were observation, questionnaires and documentation. The results of the analysis of students’ communication skills obtained an average of 81.24%, and collaboration skills obtained an average of 76.69%. Based on these results, it can be concluded that Padlet effective improving students’ communication skills and collaboration in learning Biology on the Immune System material which is included in the high category.